2013
DOI: 10.1128/aac.00874-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of GSK2485852, a Novel Hepatitis C Virus Polymerase Inhibitor

Abstract: ; GlaxoSmithKline, Collegeville, Pennsylvania, USA c GSK2485852 (referred to here as GSK5852) is a hepatitis C virus (HCV) NS5B polymerase inhibitor with 50% effective concentrations (EC 50 s) in the low nanomolar range in the genotype 1 and 2 subgenomic replicon system as well as the infectious HCV cell culture system. We have characterized the antiviral activity of GSK5852 using chimeric replicon systems with NS5B genes from additional genotypes as well as NS5B sequences from clinical isolates of patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The palm I site overlaps with the palm II site near the C316 residue, as indicated by the fact that the C316Y variant is resistant to the known palm II inhibitor HCV-796. However, HCV-796 possesses significant inhibitory activity toward genotype 2a, 2b, and 3 polymerases (18). The observation that dasabuvir is not active against genotype 2 and 3 polymerases suggests that it is likely a palm I site binder.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The palm I site overlaps with the palm II site near the C316 residue, as indicated by the fact that the C316Y variant is resistant to the known palm II inhibitor HCV-796. However, HCV-796 possesses significant inhibitory activity toward genotype 2a, 2b, and 3 polymerases (18). The observation that dasabuvir is not active against genotype 2 and 3 polymerases suggests that it is likely a palm I site binder.…”
Section: Discussionmentioning
confidence: 82%
“…Upper thumb (thumb I) binders, such as BI-207127 and BMS-791325, are associated with resistant variants P495A/S/L/T and V499A (16). The palm I and II sites are partially overlapping; palm II site inhibitors include HCV-796 and GSK5852 (17,18). HCV-796 selects a highly resistant variant, C316Y, whereas GSK5852 retains activity against C316Y but is less active against variants C316F, S365F/L/T, and C445F.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NS4B gene was amplified with the following primers for population sequencing: for genotype 1a, 5=-TCTCAGCACTTACC GTACATC-3= and 5=-CCCTTAGCCAGGAACCGGAGCATG-3=; and for genotype 1b, 5=-GCCTCACACCTCCCTTACATC-3= and 5=-CTCTT AGCCACGAGCCGGAGC-3=. Twenty-day HCV RNA reduction assay. Replicons of genotype 1b were treated with compound over a 20-day period to measure the effect of long-term dosing on replication of viral RNA, as described previously (33). Cells were seeded in flasks containing compound at a concentration of 10ϫ the calculated EC 90 .…”
Section: Methodsmentioning
confidence: 99%
“…Voitenleitner et al reported that GSK5852 showed good anti-HCV activity with EC50 values in the nanomolar range against HCV genotypes 1 and 2 and has an excellent resistant profile. This molecule is currently in clinic [147,148]. The Palm II nonnucleoside inhibitors that are currently in different phases of development are given in Table 7.…”
Section: Site IV [Palm Ii]mentioning
confidence: 99%